2022
DOI: 10.1002/pros.24443
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use and mortality in Asian, diabetic patients with prostate cancer on androgen deprivation therapy: A population‐based study

Abstract: Background This study aims to examine the associations between metformin use concurrent with androgen deprivation therapy (ADT) and mortality risks in Asian, diabetic patients with prostate cancer (PCa). Methods This study identified diabetic adults with PCa receiving any ADT attending public hospitals in Hong Kong between December 1999 and March 2021 retrospectively, with follow‐up until September 2021. Patients with <6 months of medical castration without subsequent bilateral orchidectomy, <6 months of concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Nonetheless, ADT is unlikely to be used for nonadvanced disease. 16,17 Additionally, we attempted to mitigate this by using prescription of ARSI or chemotherapy as a surrogate for metastatic disease 14,16,17,22 and performing a subgroup analysis accordingly. The results appeared qualitatively similar for most risk groups with all CIs showing substantial overlaps, supporting that the associations were likely to be independent of whether the PCa is metastatic or not.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, ADT is unlikely to be used for nonadvanced disease. 16,17 Additionally, we attempted to mitigate this by using prescription of ARSI or chemotherapy as a surrogate for metastatic disease 14,16,17,22 and performing a subgroup analysis accordingly. The results appeared qualitatively similar for most risk groups with all CIs showing substantial overlaps, supporting that the associations were likely to be independent of whether the PCa is metastatic or not.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality data were acquired from the linked Hong Kong Death Registry, a governmental mortality registry for Hong Kong citizens which records causes of death in ICD‐9 or ICD‐10 codes. Both databases have been used extensively in research and demonstrated to have good coding accuracy and data completeness 9–12 …”
Section: Figurementioning
confidence: 99%
“…Both databases have been used extensively in research and demonstrated to have good coding accuracy and data completeness. [9][10][11][12] Patients with PCa who received ADT (medical castration or bilateral orchiectomy) between 1 January 1993 and 31 March 2021 were identified. There were no exclusion criteria.…”
mentioning
confidence: 99%
“…The causes of mortality are recorded using either ICD‐9 or ICD‐10, depending on the year of death. CDARS, along with its linked mortality data, has been widely used for research purposes 14–17 . Our team has previously used this cohort of PCa patients receiving ADT for studying cardiovascular outcomes 18–20 …”
Section: Methodsmentioning
confidence: 99%